2012
DOI: 10.1080/15389588.2011.633135
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Road Traffic Injuries in Turkey

Abstract: Objective: Road traffic injuries (RTIs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
(30 reference statements)
1
11
0
1
Order By: Relevance
“…Research in Brazil found that, while only 14 % of falls were occupational, these falls were more likely to be from greater heights and result in worse injuries [ 98 ]. This is consistent with data from China that found urban falls were more likely to be from greater heights when work related and less likely to be on-level falls [ 125 ]. Finally, most research has found that occupational injuries, including falls, are more likely among men than women [ 27 , 98 ].…”
Section: Epidemiology Of Urban Fall Injuriessupporting
confidence: 80%
“…Research in Brazil found that, while only 14 % of falls were occupational, these falls were more likely to be from greater heights and result in worse injuries [ 98 ]. This is consistent with data from China that found urban falls were more likely to be from greater heights when work related and less likely to be on-level falls [ 125 ]. Finally, most research has found that occupational injuries, including falls, are more likely among men than women [ 27 , 98 ].…”
Section: Epidemiology Of Urban Fall Injuriessupporting
confidence: 80%
“…A study in 2012 says that the quality and accuracy of the data directly influence the planning of actions and in the prioritization of traffic safety while political decisions. 30 A limitation of this study was to use secondary records, with variables not informed although considered essential for the understanding of the accident. Such a situation was minimized by the relationship of data bases.…”
Section: Discussionmentioning
confidence: 99%
“…Brazil is a developing country and many studies have shown that economic growth contributes to an increase in car accidents especially among young adults, as also found in Turkey 33 . In contrast, a study in China revealed that the total number of traffic fatalities peaked in 2002, with a subsequent continued reduction, although the total number of cars has increased rapidly over the same period of time.…”
Section: ▄ Discussionmentioning
confidence: 87%